Effects of compression garments on cardiac output and leg blood flow during exercise - Wachsmuth, N. B.; Reim, F.; Bauer, F.; Galewski, P.; Maassen, N.; Schmidt, W. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Compression garments are frequently used by elite and recreational athletes, although the effects on performance are controversially discussed. Postulated effects are an enhanced oxygen supply including higher VO2max which is supposed to be due to an increased cardiac output (CO) and improved muscle perfusion. Therefore, the aim of the study was to compare VO2max, CO and blood flow of the calves during exercise with and without leg compression. Methods: 16 male triathletes and cyclists (VO2max: 64.7 ±7.3 ml/min/kg, age: 25.5 ±3.5 years) participated at the study. Every athlete completed in total 4 randomized tests on a cycle ergometer (2 incremental tests until exhaustion and 2 submaximal tests (60% of VO2max, 35min)) each of them with (C) and without (noC) compression of both legs including the thigh (CEP, medi, Germany). CO was measured before (orthostatic test), at the end of the incremental test and during the submaximal test by rebreathing a gas mixture consisting of N2O/SF6/O2 (Innovision, Denmark). Calf blood flow was determined by venous occlusion plethysmography at rest, during submaximal and immediately after submaximal and maximum exercise. Results: No difference in performance was found (VO2max, Watt, blood lactate) between C and noC. However, a marked increase of muscle blood flow was determined with compression at maximal (C: 19.9 ±3.7ml/100g, noC: 15.4 ±5.4ml/100g, p<0.01) and submaximal (C: 21.6 ±5.2ml/100g, noC: 17.8 ±5.6ml/100g, p<0.05) exercise. CO was significantly elevated in the orthostatic test with compression (C: 7.8 ±1.4l/min, noC: 7.2 ±1.2ml/min, p<0.01), showed no difference at maximum exercise and a trend to higher values (C: 21.6 ±3.6l/min, noC: 20.7 ±3.1L/min; p=008) during the submaximal test with compression. Conclusion: Although no impact of compression clothing on performance was found, physiological effects can be demonstrated. The blood perfusion of the legs was increased by 30% and CO tended to be elevated during submaximal exercise. This might be explained by a pronounced Bayliss effect and by an increased venous return. If the higher perfusion under compression is mainly due to higher skin or muscle blood flow cannot be decided here. Furthermore, the lack of increased performance remains to be clarified.